Cartoon Conflicts
XXII, 471 p. 125 illus.
Keywords: "A fascinating and unique, global account of cartooning conflicts and controversies, both historical and contemporary, written in a highly-readable, informative, and often, entertaining style." —Prof. John A. Lent, Publisher/editor-in-chief, International Journal of Comic Art “This collection of essays explores a field very often left to one side by other academics. The editors and contributors have collectively set out the stakes of historical cartoon satire. In its chronological reach and global range, the work contributes to multiple debates and shows an openness to self-questioning and reflection.” —Hugo Frey, Professor of Cultural and Visual History, University of Chichester, UK This edited collection of new research highlights the way in which the cartoon - long regarded as a staple of journalism and freedom of expression - faces new challenges in the twenty-first century that can be far better understood and appreciated if one takes an historical perspective. Current debates over the limits of freedom of expression, 'political correctness', and 'cancel culture' all have their precedents in past controversies over cartoons and caricature; indeed there is a definite continuum between these past instances of debate and their present manifestations. Richard Scully is Professor in Modern History at the University of New England, Australia. Paulo Jorge Fernandes is Assistant Professor in History at Universidade Nova de Lisboa, Portugal. Ritu Gairola Khanduri is Associate Professor in Sociology and Anthropology at the University of Texas at Arlington, USA. Chapters 2 and 10 are available open access under a Creative Commons Attribution 4.0 International License via link.springer.com.